Sobre a esfingofauna da Ilha de Maracá e da Serra de Pacaraima, Roraima (Lepidoptera, Sphingidae) - Motta, Catarina da Silva; Keppler, Ruth Leila Menezes Ferreira; Aguiar, Nair O. (Acta Amazonica, 1991)
The hawk moth species collected on Maraca island an at Pacaraima Mountain, in Roraima , are listed.